Nietzsche’s Philosophy and Buddhism: A Comparative Study - Kurniawan, Wiwit (Jurnal Ilmiah Humanika, 2020)
This study aims to explain the Buddha's teachings and philosophy Nietzsche in interpreting and contemplating the world and human suffering. Nietzsche and Buddhism, in particular aspects, have several similarities and differences that were fruitful to compare. Nietzsche was quite unaffected by Schopenhauer, who introduced Indian wisdom to the west. This paper has revealed that Buddha taught is to live with moral guidance. On the other hand, Nietzsche delivered value transvaluation to overcome suffering and nihilism conditions. Buddhism and Nietzsche had different views about desire and will. They started from quite similar initial assumptions about reality and certain ontological aspects; nevertheless, they had taken different solutions for human problems and axiological aspects.